1990
DOI: 10.1111/j.1476-5381.1990.tb14182.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of neuronal pre and postsynaptic α2‐adrenoceptor subtypes in guinea‐pig submucosal plexus

Abstract: 1 The a2-adrenoceptors on cell bodies of submucosal neurones, on presynaptic cholinergic nerve terminals innervating submucosal neurones, and on presynaptic sympathetic fibres innervating submucosal arterioles were characterized in functional studies by use of subtype selective ligands. 2 Both membrane hyperpolarization and presynaptic inhibition of nicotinic excitatory synaptic potentials (e.p.s.ps) produced by UK 14304 were similarly antagonized by idazoxan, yohimbine, SKF 104078, WB 4101 and ARC-239. Antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
3
14
1
Order By: Relevance
“…This is despite the fact that both in the present and a previous study (Shen et al, 1990) NA has been demonstrated to be released from sympathetic nerves in the submucosal plexus following nerve stimulation and activates inhibitory prejunctional M2-adrenoceptors on both submucosal and sympathetic neurones. Moreover, vasoconstrictions of similar amplitude to the neurogenic response can be evoked by the exogenous application of low concentrations of a-adrenoceptor agonists (Shen et al, 1990;Vanner et al, 1990). Resistance to a-adrenoceptor blockade is not a new phenomenon and has been described in many vascular tissues (for review, see Burnstock, 1990).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This is despite the fact that both in the present and a previous study (Shen et al, 1990) NA has been demonstrated to be released from sympathetic nerves in the submucosal plexus following nerve stimulation and activates inhibitory prejunctional M2-adrenoceptors on both submucosal and sympathetic neurones. Moreover, vasoconstrictions of similar amplitude to the neurogenic response can be evoked by the exogenous application of low concentrations of a-adrenoceptor agonists (Shen et al, 1990;Vanner et al, 1990). Resistance to a-adrenoceptor blockade is not a new phenomenon and has been described in many vascular tissues (for review, see Burnstock, 1990).…”
Section: Discussioncontrasting
confidence: 83%
“…Studies on guinea-pig submucosal arterioles have shown that both the underlying changes in membrane potential (excitatory junction potentials, ej.ps) and vasoconstrictions following short trains of low or high frequency stimulation of the sympathetic nerves are unaffected by ax-adrenoceptor antagonists (Hirst & Neild, 1980;1981;Shen et al, 1990). Paradoxically these vessels constrict when low concentrations of NA are applied exogenously, and NA released from the sympathetic nerves following electrical stimulation acts through prejunctional a2-adrenoceptors to depress transmitter release.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is unclear, especially since it has been reported that ARC 239 acted as neither agonist nor antagonist of the neurally evoked vasoconstriction in submucosal arterioles. In this tissue low concentrations of ARC 239 (1 and 3 nM) shifted the concentration-effect curves to clonidine and UK 14,304 to the left (Shen et al, 1990).…”
Section: Transmural Stimulationmentioning
confidence: 81%
“…Dilatations in response to stimulation for 10 s at 10 Hz given at intervals of 15-20 min were of similar magnitude for up to 4 h and ranged from 10 to 40 % of the preconstricted diameter. The latency to onset of stimulation-evoked vasodilatation was 1P5-3 s; this is approximately 10 times slower than the latency to onset of the sympathetic vasoconstriction (0-3-0-6 s) measured in these arterioles using the same stimulus applied to the sympathetic nerve fibre bundles (see also Shen, Barajas-Lopez & Surprenant, 1990) NG-Monomethyl-L-arginine (L-NMMA), a nitric oxide synthase inhibitor (Rees, Palmer, Hodson & Moncada, 1989), decreased the neurogenic cholinergic vasodilatation in a dose-dependent fashion with maximum inhibition occurring at a concentration of 300 /LM (Fig. 2).…”
Section: Cholinergic Vasodilatations In Response To Ganglionic Stimulmentioning
confidence: 99%